The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/10646175.2013.805991
|View full text |Cite
|
Sign up to set email alerts
|

Reporting on Health to Ethnic Populations: A Content Analysis of Local Health News in Ethnic Versus Mainstream Newspapers

Abstract: Ethnic newspapers seek to provide local news not provided by other media, yet few studies have compared local health news in ethnic versus mainstream newspapers. Local health news in ethnic newspapers could decrease health disparities among ethnic communities who are at higher risk for certain chronic illnesses and diseases. Localized story elements could inform ethnic audiences and broaden the discussion about local health issues, shedding light on priorities of ethnic media in providing relevant health infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Finally, our study demonstrated that news coverage of health issues in a rural community lacked information that would help make the news useful as a vehicle for health promotion information, suggesting that despite the promise of newspapers to serve as health communication channels, there is much opportunity to grow to realize that promise. Both of these patterns are consistent with previous content analyses of California newspapers in general (Wang & Rodgers, 2013) as well as Latino-targeted newspapers in particular (Vargas & dePyssler, 1999). …”
Section: Discussionsupporting
confidence: 89%
“…Finally, our study demonstrated that news coverage of health issues in a rural community lacked information that would help make the news useful as a vehicle for health promotion information, suggesting that despite the promise of newspapers to serve as health communication channels, there is much opportunity to grow to realize that promise. Both of these patterns are consistent with previous content analyses of California newspapers in general (Wang & Rodgers, 2013) as well as Latino-targeted newspapers in particular (Vargas & dePyssler, 1999). …”
Section: Discussionsupporting
confidence: 89%
“…They also recorded information about the story author and geographical area discussed (see Table 4 for examples). Although these quantitative data allow us to gauge whether the story was local, they do not necessarily reflect localization, which has been defined as the process of including local story elements, such as local sources or statistics (24, 28). …”
Section: Methodsmentioning
confidence: 99%
“…Similar to mainstream local media, ethnic media perform a social-control function by reinforcing community norms and downplaying community conflict to promote stability; they also perform an informational function by surveilling and disseminating relevant content to communities (30). Perhaps more importantly, ethnic media are particularly trusted and influential sources of health information, primarily because they are able to achieve both personal and community relevance through localization and other targeting strategies (24, 31, 32). Although some have questioned whether they have yet to fully realize their potential as a critical health information source (24, 33), it is important to examine disparities/SDH coverage in these sources, given their centrality to communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent scholarship on cancer news coverage suggests that ethnic newspapers are promising outlets for the dissemination of cancer control messages (Stryker, Emmons, & Viswanath, 2007), although research finds these newspapers often fall short of providing health news relevant to specific audiences (Wang & Rodgers, 2013). Ethnic newspapers offer information that require lower literacy levels to understand (Stryker et al, 2007), which may make these news outlets more accessible to certain subpopulations, such as Latino(a)/Hispanic (henceforth referred to as Latino) immigrant populations that have lower literacy levels (Dunn-Navarra, Stockwell, Meyer, & Larson, 2012) and/or lower English language proficiency (Sentell & Braun, 2012).…”
mentioning
confidence: 99%